Tapered plastic optical fiber coated with ZnO nanostructures for the measurement of uric acid concentrations and changes in relative humidity - Batumalay, M. (Elsevier, 2014)
Simple sensors are proposed and demonstrated using a tapered POF coated with ZnO nanostructures for measurement of different concentrations of uric acid in de-ionized water and changes in relative humidity (RH). The sensor operates based on intensity modulation technique. The tapered POF were fabricated by etching method using acetone, sand paper and de-ionized water to achieve a waist diameter of 0.45 mm and tapering length of 10 mm. The tapered fiber were then coated with ZnO nanostructures using sol-gel immersion method on ZnO seeded and non-seeded fiber. As the concentration of the uric acid was varied from 0 ppm to 500 ppm, the output voltage of the sensor using tapered POF with seeded ZnO nanostructures increased linearly with a higher sensitivity of 0.0025 mV/ppm compared to 0.0009 mV/ppm for unseeded tapered POF coated with ZnO. Both samples showed almost similar linearity of the response cuves of about 98.2%. The tapered POF with ZnO nanostructures interact with uric acid due to strong electrostatic interaction resulting in the increase in response with the increasing concentration. In addition, the seeded ZnO nanostructure could significantly enhance the transmission of the sensor that is immersed in solutions of higher concentration. On the other hand, for both samples, the change in the intensity of the transmitted light of the tapered POF coated with ZnO nanostructures decreases linearly with relative humidity. The tapered POF with grown (seeded) ZnO provides better sensitivity at 0.0258 mV/% with a slope linearity of 95.48%. The ZnO nanostructures that are exposed to an environment of humidity causes rapid surface adsorption of water molecules and changes in optical properties. The tapered POF coated with ZnO nanostructures using the seeding technique causes an increase in both effective RI of surrounding medium and absorption coefficient of the ZnO nanostructures surfaces and leads to larger leakage of light. Results show that tapered POF with seeded ZnO nanostructures enable to increase the sensitivity of fiber for uric acid detection as well as relative humidity. The proposed sensors provide numerous advantages such as simplicity of design, low cost of production, higher mechanical strength and easier to handle compared to silica fiber optic.